Effect of nasal and sinus surgery on sleep quality at the Hospital Edgardo Rebagliati Martins during 2017 - Alcas, Olenka (2019)
Objective: To determine the effect of nasal and sinus endoscopic surgery on sleep quality at the Otorhinolaryngology Department of the Hospital Edgardo Rebagliati Martins during 2017. Materials and methods: A retrospective and longitudinal study was conducted with a sample of 92 patients who underwent surgery and whose sleep quality was assessed using the Pittsburgh Sleep Quality Index. The data was analyzed using software SPSS version 24. Additionally, a univariate analysis, Mann-Whitney U test, Spearman´s rank correlation coefficient and Wilcoxon signed rank test were used in the study. Results: Both sleep quality (p <0.01) and nasal obstruction (p <0.01) improved after nasal and sinus endoscopic surgery. The preoperative data shows that BMI (body mass index) and nasal obstruction have a correlation with sleep quality. Conclusions: Nasal and sinus endoscopic surgery had a positive effect on sleep quality in patients of the Otorhinolaryngology Department of the Hospital Edgardo Rebagliati Martins during 2017.